Religious Sources of Defence-Spending Attitudes in the United States and the Case of Evangelical Distinctiveness. (3rd July 2019) - Roy, Oindrila
ABSTRACT: Conventional wisdom suggests religious affiliation—especially evangelical identity—is directly instrumental in driving a distinct set of foreign policy preferences in the United States. I test this line of argument by examining the religious roots of defence-spending attitudes between 1982 and 2008. Using the Karlson, Holm, and Breen (KHB) method along with a series of regression estimates, I find the association of religious factors with such perceptions is more complicated than the straightforward logic of the conventional wisdom. While I find support for evangelical distinctiveness, I also find public perceptions divided across religious traditions along the lines of a specific form of religious belief and behaviour. Moreover, I obtain substantial mediated relationships between the religious variables and defence-spending attitudes via party ID and ideology. Finally, while comparing over time change in defence-spending attitudes across religious groups as well as presidential administrations, I find limited support for the claim that evangelicals demonstrated distinct preferences during President George W. Bush's administration as compared to that under his predecessors since 1982.